Crimean-Congo Hemorrhagic Fever in Iraq During 2010: Emad S. Abul-Eis , Nabeel A.Mohammad and Suhad M.Wasein - Abul-Eis , Emad S. (The Iraqi Journal of Veterinary Medicine, 2012)
Crimean-Congo hemorrhagic fever (CCHF) is a viral zoonotic disease with a highmortality rate in humans. CCHF is caused by genus Nairovirus, in family of Bunyaviridae,and is transmitted to humans through the bite of ticks Hyalomma spp or contact with blood ortissues of CCHF patients or infected livestock.The total numbers of positive patients to CCHF virus was 11 out of 44 suspected sampleswere examined from eight provinces during the period from January to December 2010 . Theway of transmission is due to contact with blood and tissues of infected animals, and onepatient slaughtered sheep in his house. ELISA was used to detect Crimean-Congohemorrhagic fever (CCHF) virus-specific immunoglobulin M (IgM) in human serum samples.